Establishing and Evaluating Equitable Partnerships - James E. McLean; Bruce A. Behringer (The University of Alabama, 2022)
In this paper, the authors present two models for establishing and evaluating partnerships. They also provide a working definition of a partnership, propose strategies for identifying resources for starting and maintaining partnerships, and provide several methods for evaluating them. Their purpose is to increase understanding of the dynamics of building stronger, more equity-based partnerships. Models recommended are the Give-Get and Double Rainbow.